COGNITIVE COMPETENCE COMPARED TO COGNITIVE INDEPENDENCE AND COGNITIVE ACTIVITY - Irina B. Shmigirilova (Образование и наука)
The research is aimed at identifying the essence of the cognitive competence concept in comparison with the concepts of cognitive independence and activity.Methods: The methodology implies a theoretical analysis of psychopedagogical and methodological materials on the cognitive competence formation; generalized teaching experience; empirical methods of direct observations of educational process in the secondary school classrooms; interviews with school teachers and pupils.Results: The research outcomes reveal a semantic intersection between the cognitive competence, independence and activity, and their distinctive features. The paper emphasizes the importance of cognitive competence as an adaptive mechanism in situations of uncertainty and instability.Scientific novelty: The author clarifies the concept of cognitive competence regarding it as a multi-component and systematic characteristic of a personality.Practical significance: The research findings can be used by specialists in didactics developing the teaching techniques of cognitive competence formation for schoolchildren.